Enhanced chloride-free snow-melting agent generation from organic wastewater by integrating bioconversion and synthesis. (December 2022) - Wang, Yijie; Huang, Zhenxing; Zhao, Mingxing; Miao, Hengfeng; Shi, Wansheng; Ruan, Wenquan
Graphical abstract: Highlights: Organic wastewater was converted into snow-melting agents as high-value products. The highest TVFAs of 45.9 g/L was obtained at an OLR of 5 g COD/(L·d) in the iMBR. CSAs were 78.4% and 94.7% less corrosive to metals and concrete compared to CaCl2 . Abstract: In this study, a new process for producing chloride-free snow-melting agents (CSAs) was proposed. Organic wastewater was converted to total volatile fatty acids (TVFA) by anaerobic acidogenic fermentation. The experiments for acid generation showed that the maximum TVFA concentration of 45.9 g/L was obtained at an organic loading rate of 5 g chemical oxygen demand /(L·d), and the proportion of acetic acid reached 78.8 %. Forward osmosis was used for concentrating the TVFA solution. The obtained CSAs, after evaporation and crystallization, had a better ice-melting capacity and less corrosion on metal and concrete than NaCl and CaCl2 . Additionally, the damage caused by CSAs to the germination of plant seeds was significantly lesser than that caused by chloride salts. This study proposed a feasible method for the high-value conversion of organic wastewater, providing a new direction for the reuse of organic wastewater.